anagement of Open Diaphyseal Fracture of Tibia with Plaster of Paris (Pop) Cast Vs External Fixator in A Tertiary Care Centre - Allah Nawaz Abbasi, Syed Karam All Shah, Zahoor Wahl Soomro (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective:To determine the management of open diaphyseal fracture of tibia with plaster of paris (pop) cast vs external fixator ina tertiary care center. Methods:T his study was carried out in the Orthopedic department, Peoples University of Medical and Health Sciences Nawabshahfor the period of 18 months, from January 2015 to June 2016. A total of 50 patients were included in the study, selected on the basis of inclusion criteria. Patients were divided in two groups of equal number. 25 patients in Group A, treated by conservative method with plaster of paris cast and 25 patients in group B treated by external fixator .Two groups of patients were randomly selected. All the patients were managed as an emergency and when stabilized, sample for culture and sensitivity was sent if required. Wound debridement and stabilization of fracture with external fixator or plaster of paris (pop) cast. Open fractures were fixed with either of the above said two methods. Post operative antibiotics were changed according to culture and sensitivity report. Results: Out of 50 patients with tibial diaphyseal fractures, there were 34 males compared to females 16 (2.1:1) (68% vs 32%) with an average age of 41 years. Patients with external fixator applied yielded decreased rates of infection; shorter duration of hospital stay and early union compared to patients with plaster of paris(pop)cast application. However the difference did not reach statistical significant value. Conclusion: Plaster cast is the initial treatment of modality in patients with open tibial diaphyseal fractures, but these fractures should be managed with external fixation that yields better results.